Stimulation of nitrogen-hydrolyzing enzymes in soil aggregates mitigates nitrogen constraint for carbon sequestration following afforestation in subtropical China. (August 2018) - Feng, Jiao; Wu, Junjun; Zhang, Qian; Zhang, Dandan; Li, Qianxi; Long, Chunyan; Yang, Fan; Chen, Qiong; Cheng, Xiaoli
Abstract: Soil nitrogen (N) availability is a major constraint for plant growth and consequently impacts soil carbon (C) sequestration following afforestation. The transformation of soil organic N to plant available form is predominantly catalyzed by N-hydrolyzing enzymes. Yet how N-hydrolyzing enzymes affect N availability for soil C sequestration under afforestation remains unclear. Here, we examined N-hydrolyzing enzyme activities, N masses (N contents in equivalent soil mass) and the δ 15 N values of total N (TN) pool and stable N pool (SN, NaOCl–resistant) in soil aggregates following 30 years of afforestation in subtropical China. The relationships of soil N mass and supply via enzymes with those of C were also developed. Afforestation increased TN masses and N-hydrolyzing enzyme activities, but declined the percentages of SN in TN and the δ 15 N values in soil aggregates. Soil TN mass was positively correlated with soil organic C mass in aggregates across land use types. Similarly, soil enzymes for N acquisition scaled isometrically with C acquisition with a slope of ∼1.0. Our results indicate that N constraint for soil C sequestration can be alleviated by increasing soil N-hydrolyzing enzyme activities combined with reducing SN:TN ratios and homeostatic ecoenzymatic C:N ratios following afforestation, which lead to tight coupling of soil N and C cycling. Highlights: Afforestation generally enhanced enzyme activity and TN mass in all soil aggregates. Afforestation generally reduced stable N:TN and δ 15 N values in all soil aggregates. TN mass in soil aggregates correlated positively with SOC mass across land use. N- and C-hydrolyzing enzyme activities were positively correlated across land use.